TUMOR NECROSIS FACTOR-α INHIBITORS IN THE TREATMENT OF AXIAL SPONDYLOARTHRITIS, INCLUDING ANKYLOSING SPONDYLITIS - S. A. Lapshina; T. V. Dubinina; V. V. Badokin; A. G. Bochkova; O. V. Bugrova; I. Z. Gaidukova; A. A. Godzenko; A. A. Dubikov; O. N. Ivanova; T. V. Korotaeva; O. B. Nesmeyanova; I. P. Nikishina; et al. (Научно-практическая ревматология, 2016)
The paper provides guidelines for the use of tumor necrosis factor-α  (TNF-α) inhibitors in the treatment of patients with axial spondyloarthritis  (axSpA), including ankylosing spondylitis. It gives data on the efficacy of TNF-α inhibitors in patients with non-radiographic axSpA. By using international and Russian guidelines, the authors lay down indications for this therapy and criteria for evaluation of its efficiency and safety.